p97/VCP is required for piecemeal autophagy of aggresomes - Maria Körner; Paul Müller; Hirak Das; Felix Kraus; Timo Pfeuffer; Sven Spielhaupter; Silke Oeljeklaus; Christina Schülein-Völk; J. Wade Harper; Bettina Warscheid; Alexander Buchberger (Nature Communications)
Abstract Metazoan cells adapt to the exhaustion of protein quality control (PQC) systems by sequestering aggregation-prone proteins in large, pericentriolar structures termed aggresomes. Defects in both aggresome formation and clearance affect proteostasis and have been linked to neurodegenerative diseases, but aggresome clearance pathways are still underexplored. Here we show that aggresomes comprising endogenous proteins are cleared via selective autophagy requiring the cargo receptor TAX1BP1. TAX1BP1 proximitomes reveal the presence of various PQC systems at aggresomes, including Hsp70 chaperones, the 26S proteasome, and the ubiquitin-selective unfoldase p97/VCP. While Hsp70 and p97/VCP with its cofactors UFD1-NPL4 and FAF1 play key roles in aggresome disassembly, the 26S proteasome is dispensable. We identify aggresomal client proteins that are degraded via different routes, in part in a p97/VCP-dependent manner via aggrephagy. Upon acute inhibition of p97/VCP, aggresomes fail to disintegrate and cannot be incorporated into autophagosomes despite the presence of factors critical for aggrephagosome formation, including p62/SQSTM1, TAX1BP1, and WIPI2. We conclude that the p97/VCP-mediated removal of ubiquitylated aggresomal clients is essential for the disintegration and subsequent piecemeal autophagy of aggresomes.